NATURAL ADVENTUROUS PHYSICAL ACTIVITIES IN SÃO LUIS CITY: NATURE AS A SCENARIO AND NOT AS A SENSE (Fiep Bulletin - online, 2012)
Introduction: Natural adventurous physical activities permit an interaction between human and nature, providing well-being, life quality and socialization. Aim: Identifying natural adventurous physical activities and their place to be practice and describing the reality of the practice in São Luís City-MA. Methodology: Qualitative research, whose instrument for data collection has been a semi-structured interview applied to adventurous activities practitioners in São Luís City. Results: The city has favorable geography for the practice of these activities and there is no incentive which provides better infra-structure, cleanliness and safety in the practice locations. Discussion: Natural activities have got impulse with the speech of environmental preservation, which was attached to these activities’ practitioners, who do it in order to get closer to nature and ecotourism. However, it is not what is realized in local practitioners’ speeches. Conclusion: It has been seen that these activities have grown in the city due to its geographical and climate conditions; however, there is little incentive and no disclosure. The people who practice these sports start to do it by friends’ influence.
Keywords: Activities; Adventure; São Luís